Natural Resource Abundance, Growth and Diversification in MENA : The Effects of Natural Resources and the Role of Policies - Diop, Ndiame; Marotta, Daniela; de Melo, Jaime (World Bank, Washington, DC, 2014)
The Middle East and North Africa (MENA) region is one of the richest in the world in terms of natural resources. It holds more than 60 percent of the world's proven oil reserves, mostly located in the Gulf region, and nearly half of global gas reserves. Not surprisingly, oil represents close to 85 percent of the merchandise exports of the region, making it highly susceptible to fluctuations in international prices. A long strand of economic literature suggests that such dependence may hurt a country's growth prospects and job creation by reducing the scope for economic diversification. A forthcoming WB publication investigates how MENA can overcome this challenge and encourage greater economic diversification. The study examines the pattern of structural transformation in MENA and explores the role of natural resources and macroeconomic policies in driving the current (limited) diversification outcomes. The authors explore analytical questions, such as: (i) the impact of the real exchange rate on manufacturing and tradable services competitiveness in MENA; (ii) the role of fiscal policy in supporting diversification; (iii) how 'weak links' (input sectors with low productivity) play a critical role in explaining the concentration of economic activities, in addition to the classical Dutch disease effect; and (iv) the impact of macroeconomic factors on the drive for regional integration. The main findings are summarized in this quick note. The study highlights that the negative effect of rents is compounded by the negative impact of policy and regulatory restrictions on entry, and of business conduct on the development of services sectors.